Manajemen Keuangan dan Strategi Pemasaran sebagai Upaya Meningkatkan Kemandirian Santri di Pondok Pesantren Al-Muqriyah - Astri Cahya Melani; Wanda Hamidah V; Yuwa Harrist Estu S (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The importance of economic independence for students who are also pursuing formal education at the high school and vocational high school levels is the background to this community service activity. The main problem at the Al-Muqriyah Islamic Boarding School is the lack of practical understanding of business financial management and product marketing strategies, which are still conventional. This activity aims to equip students with financial management and digital marketing competencies to increase their independence. The method used was intensive training (a one-day workshop) that included material presentations, simple bookkeeping simulations, and practical promotional content creation. The results of the activity showed an increase in participants' understanding of cash flow management and skills in optimizing social media as a marketing tool. In conclusion, strengthening this managerial aspect is a strategic step to foster the entrepreneurial spirit of students. The sustainability of this program is crucial for the Islamic boarding school business unit to develop professionally and provide a real economic impact on the Islamic boarding school environment.